2013
DOI: 10.15288/jsad.2013.74.406
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Alcohol Use Disorders and Suicidal Ideation in Young Women

Abstract: ABSTRACT. Objective: Alcohol use disorders (AUDs) and suicidal ideation (SI) co-occur, yet few studies have investigated the risk and protective factors that infl uence their comorbidity. Method: Data from 3,787 twin women ages 18-27 years were analyzed. AUD was defi ned as a lifetime history of alcohol abuse or dependence as defi ned in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition. SI was coded as a lifetime report of any SI, and all subjects were queried about SI. Subjects were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
2
10
1
Order By: Relevance
“…We also found that the specific comorbid conditions of obesity and alcoholism were associated with increased risk of an SII, results that align with other research on selfharm behavior in adolescents. 14,15 We found that risk of SII was lower in African American adolescents than in white adolescents, which differs from previous research. Cooper et al found that rates of self-harm in patients presenting to EDs in 3 English cities were highest in young black females, 20 whereas Ting et al found that blacks in the United States had higher population rates of ED visits for attempted suicide and SII compared with whites.…”
Section: Figurecontrasting
confidence: 99%
See 2 more Smart Citations
“…We also found that the specific comorbid conditions of obesity and alcoholism were associated with increased risk of an SII, results that align with other research on selfharm behavior in adolescents. 14,15 We found that risk of SII was lower in African American adolescents than in white adolescents, which differs from previous research. Cooper et al found that rates of self-harm in patients presenting to EDs in 3 English cities were highest in young black females, 20 whereas Ting et al found that blacks in the United States had higher population rates of ED visits for attempted suicide and SII compared with whites.…”
Section: Figurecontrasting
confidence: 99%
“…It is possible that adolescents with SII visits were more likely to be diagnosed with alcoholism or obesity if these conditions were thought to be causally linked with the self-harm behavior. However, other studies have found associations between alcoholism or obesity and SII, 14,15 providing support for our findings.…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…Of the 168 references considered potentially eligible after screening, 137 studies were excluded because they were not original article (i.e., letter, commentary, review) or did not meet the inclusion criteria ( Fig 1 ). Eventually, 31 studies included in the meta-analysis, including 9 cohort studies [ 23 31 ] and 10 case-control studies [ 32 41 ] and 12 cross-sectional studies [ 42 53 ]. All included studies were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of suicidal ideation was a predictive variable for longer treatment adherence time, and women reporting this condition had a 2.7-times higher chance of remaining in treatment than those who denied such a condition. The high prevalence of suicidal ideation found among women in this study may be related to the number of women who associated MDE and MDI with alcohol, whose dependence has been related to a greater chance of presenting suicidal ideation than those who are not dependent on this substance (25) . Suicidal ideation as a predictor of treatment adherence is a fact that has not been found in other published studies involving this population, and therefore has not aroused research interest until now.…”
Section: Discussionmentioning
confidence: 73%